1996
DOI: 10.1111/j.1439-0388.1996.tb00606.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperament and reproductive success in farmbred silver foxes housed with and without platforms

Abstract: Summary Human, strike, pencil, confrontation, feeding, and disturbance tests were used to study fear‐motivated behaviour in farmed silver foxes (Vulpes vulpes), housed with and without wooden platforms. The results showed that the number of fearful animals was highest and lowest in the confrontation and feeding tests, respectively. Foxes that had used platforms most frequently before the behavioural tests, were also most often found on platforms during the tests. Temperament differences between control and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…Since the late 1960s, research by Belyaev has demonstrated that selective breeding in foxes Vulpes vulpes produced major shifts in morphology, physiology and temperament (Belyaev, 1979;Trut, 1999). Since then, a number of studies have documented this rapid evolution in a number of captive populations as a result of artificial selection (fox, Korhonen & Niemela, 1995;mink, Hansen, 1996; mouse Mus musculus, DeFries, Gervais & Thomas, 1978;great tit, Drent et al, 2003;van Oers, Drent & van Noordwijk, 2004;poultry, Faure & Mills, 1998). This form of directed and methodical selection should only occur in non-conservation initiatives; studies have proposed this approach to facilitate the management of permanently captive populations in zoos (Aengus & Millam, 1999;van Heezik & Seddon, 2001).…”
Section: Evolutionary Changes In Captivity and Consequences For Reintmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the late 1960s, research by Belyaev has demonstrated that selective breeding in foxes Vulpes vulpes produced major shifts in morphology, physiology and temperament (Belyaev, 1979;Trut, 1999). Since then, a number of studies have documented this rapid evolution in a number of captive populations as a result of artificial selection (fox, Korhonen & Niemela, 1995;mink, Hansen, 1996; mouse Mus musculus, DeFries, Gervais & Thomas, 1978;great tit, Drent et al, 2003;van Oers, Drent & van Noordwijk, 2004;poultry, Faure & Mills, 1998). This form of directed and methodical selection should only occur in non-conservation initiatives; studies have proposed this approach to facilitate the management of permanently captive populations in zoos (Aengus & Millam, 1999;van Heezik & Seddon, 2001).…”
Section: Evolutionary Changes In Captivity and Consequences For Reintmentioning
confidence: 99%
“…The primary objectives of enrichment are to avoid undesirable behaviours associated with stress in captivity -stereotypies and high aggression -and to encourage individuals to behave naturally (Carlstead, 1996). Studies have reported significant reduction in stress after environmental enrichment (Korhonen & Niemela, 1995), but few considered how this enrichment could interact with temperament. Despite increasing the overall reproductive success of a captive population, enrichment risks introducing increased variation by enhancing the fitness of a particular genotype or set of temperament traits (Fig.…”
Section: Avoiding Evolutionary Change In Breeding Programmesmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperament affects fitness through influences on predation rates, competition for mates and resources, and social interactions (reviewed by Smith and Blumstein 2008;May et al 2016). For example, variation in neophobia has been linked with reproductive output in farmed silver foxes (V. vulpes) (Korhonen and Niemelä 1996), and variation in boldness has been linked with post-translocation survival in swift foxes (Vulpes velox) (Bremner-Harrison et al 2004).…”
Section: Innate Avoidance Of Baitsmentioning
confidence: 99%